Human Interaction with Machines Proceedings of the 6th International Workshop held at the Shanghai JiaoTong University, March 15-16, 2005 - Hommel, G.; Huanye, Sheng; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2006)
The International Workshop on “Human Interaction with Machines” is the sixth in a successful series of workshops that were established by Shanghai Jiao Tong University and Technische Universität Berlin. The goal of those workshops is to bring together researchers from both universities in order to present research results to an international community. The series of workshops started in 1990 with the International Workshop on “Artificial Intelligence” and was continued with the International Workshop on “Advanced Software Technology” in 1994. Both workshops have been hosted by Shanghai Jiaotong University. In 1998 the third wo- shop took place in Berlin. This International Workshop on “Communi- tion Based Systems” was essentially based on results from the Graduiertenkolleg on Communication Based Systems that was funded by the German Research Society (DFG) from 1991 to 2000. The fourth Int- national Workshop on “Robotics and its Applications” was held in Sha- hai in 2000. The fifth International Workshop on “The Internet Challenge: Technology and Applications” was hosted by TU Berlin in 2002.
Reference Points for the Observation of Systems Behaviour -- Efficient Text Categorization Using a Min-Max Modular Support Vector Machine -- A Self-healing Protocol Stack Architecture for Bluetooth® Wireless Technology -- From Keyframing to Motion Capture -- Multi-Modal Machine Attention: Sound Localization and Visual-Auditory Signal Synchronization -- A note on the Berlin Brain-Computer Interface -- Segmentation of Brain MR Images Using Local Multi-Resolution Histograms -- EMG-Driven Human Model for Orthosis Control -- Virtual Information Center for Human Interaction -- Reduced Human Interaction via Intelligent Machine Adaptation -- A Novel Watershed Method Using Reslice and Resample Image -- Stable Motion Patterns Generation and Control for an Exoskeleton-Robot -- A Study on Situational Description in Domain of Mobile Phone Operation -- Computer-Supported Decision Making with Object Dependent Costs for Misclassifications -- Robust Analysis and Interpretation of Spoken Chinese Queries -- Development and Control of a Hand Exoskeleton for Rehabilitation -- Automatically Constructing Finite State Cascades for Chinese Named Entity Identification -- Improving Information Retrieval by Concept-Based Ranking -- Liver Perfusion using Level Set Methods.
Keywords: Electrical engineering; Special purpose computers; User interfaces (Computer systems).; Application software; Electrical Engineering; Special Purpose and Application-Based Systems; User Interfaces and Human Computer Interaction; Computer Applications